'The Eikaiwa/ALT Black Hole. A Corpus Linguistic approach to analysis of NESTs' informal online discourse relevant to teacher development in Japan - Kirkwood, Hugh (2015)
Native English-Speaking Teachers (NESTs) in Japan are often employed by private language schools (known as eikaiwa) and work as Assistant Language Teachers (ALTs) in public schools. Teachers working, or seeking to work, in these contexts may use the Internet to exchange informal online communications or view the communications of others. This study suggests analysis of this online discourse can provide insights into these teachers’ context specific knowledge, and these insights can contribute to efforts to understand and improve NEST teacher development in Japan. In attempting to develop a framework for this analysis, Internet sites hosting large quantities of these informal communications were identified and used to provide texts for a corpus of teachers’ informal online discourse. Key words in this discourse were then identified using corpus software and a larger reference corpus. Subsequent analysis of these key words within Key Word In Context (KWIC) lines identified frequent expressions of dissatisfaction with eikaiwa and ALT work and a sense that working in these contexts impeded the development of NESTs’ teaching identities and careers. The analysis also drew attention to the importance of teachers’ knowledge of employment conditions as exchanges of information required to enter and leave eikaiwa and ALT featured prominently in teachers’ discourse. The results of this analysis suggest that accessing informal online discourse may help NESTs achieve their career and development goals, but they also suggest that the employment prospects of NESTs seeking long-term positions in Japan are becoming increasingly uncertain and subject to increased competition.